The Peter F. Drucker reader : - Drucker, Peter F. (Harvard Business Review Press, 2017)
Peter Drucker revolutionized management thinking before there was management thinking. For nearly half a century he inspired and educated managers--and powerfully shaped the nature of business--with his landmark articles in Harvard Business Review. Through Drucker's unique lens, this volume presents a rare opportunity to trace the evolution of the great shifts in organizations and to grasp more firmly the role of managers in the ongoing effort to balance change with continuity. The book also offers managers and executives a collection of best practices as well as introspective questions that will help them improve as organizational leaders. Infused with a perspective that holds new relevance today, these selections reveal a celebrated thinker at his best.